Pseudo Landau levels, negative strain resistivity, and enhanced thermopower in twisted graphene nanoribbons - Zheng Shi; Hai-Zhou Lu; Tianyu Liu (Physical Review Research, 2021)
As a canonical response to the applied magnetic field, the electronic states of a metal are fundamentally reorganized into Landau levels. In Dirac metals, Landau levels can be expected without magnetic fields, provided that an inhomogeneous strain is applied to spatially modulate electron hoppings in a way similar to the Aharonov-Bohm phase. We here predict that a twisted zigzag nanoribbon of graphene exhibits strain-induced pseudo Landau levels of unexplored but analytically solvable dispersions at low energies. The presence of such dispersive pseudo Landau levels results in a negative strain resistivity characterizing the (1+1)-dimensional chiral anomaly if partially filled and can greatly enhance the thermopower when fully filled.